TMPRSS2-ERG confers resistance to antiandrogens: mechanism and therapeutic implications - Sekar, Arunachalam; Chatterjee, Rishita; Selvadurai, Boobash Raj; Pal, Lipika R; Verma, Aakanksha; Nataraj, Nishanth Belugali; Garcia, Diana Drago; Giri, Suvendu; Genna, Alessandro; Karatekin, Feride; Gupta, Nitin; Zerbib, Mirie; et al. (bioRxiv, 2025)
Approximately 50% of prostate cancer (PCa) patients harbor fusions involving the and genes. Despite this, tailored therapies targeting the fused gene, , remain undeveloped. Our study analyzed biopsy samples from two clinical trials assessing the efficacies of androgen receptor (AR) signaling inhibitors (ARSIs). The results revealed that promotes resistance to ARSIs and is associated with elevated levels of the glucocorticoid receptor (GR). Subsequent assays showed that GR directly interacts with tERG, alleviates allosteric autoinhibition and prevents chemotherapy-induced tERG degradation. In PCa models, either inhibiting GR or lowering cortisol levels suppressed tumor growth in tERG-positive models, but not in fusion-negative models. In addition, patient-derived fusion-positive xenografts displayed enhanced sensitivity to combined GR and AR inhibitors. Collectively, these findings highlight as a new biomarker and propose that simultaneous inhibition of GR and AR may specifically benefit -positine patients. However, GR stimulatory corticosteroid therapies may not be advisable for this patient subgroup.